Fitorremediaciòn de las Aguas Residuales generadas en la Parroquia Canchagua mediante la utilización de dos Especies Vegetales en el Cantón Saquisilí, periodo 2015 - Toapanta Del Valle, María José (2017)
The present research project was carried out in the Province of Cotopaxi and we aimed to evaluate two plant species for the remediation of wastewater in Canchagua Parish, Saquisilí canton, in the period 2015, studies carried out using several methodologies, the same ones that were The fundamental basis for organizing the concepts and criteria to contribute to the development of this subject that allowed to know the current state of the treatment plant, to support the proposal was made a physical, chemical analysis of water in the laboratory of DHSOLAMBI SA, the The same ones that were carried out applying the protocol established in the INEN Standard, for the chemical parameters such as: Hydrogen Potential, Sulphates, Nitrates, Nitrites, Biochemical Oxygen Demand, Oxygen Chemical Demand, Chlorides, Dissolved Solids, Suspended Solids, parameters Physics: Conductivity, Color, Results Compared With the respective regulations, obtaining the interpretation as follows: of the 9 chemical